2012
DOI: 10.1210/en.2011-1794
|View full text |Cite
|
Sign up to set email alerts
|

Differential Entrainment of Peripheral Clocks in the Rat by Glucocorticoid and Feeding

Abstract: The suprachiasmatic nucleus is the master circadian clock and resets the peripheral clocks via various pathways. Glucocorticoids and daily feeding are major time cues for entraining most peripheral clocks. However, recent studies have suggested that the dominant timing factor differs among organs and tissues. In our current study, we reveal differences in the entrainment properties of the peripheral clocks in the liver, kidney, and lung through restricted feeding (RF) and antiphasic corticosterone (CORT) injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
69
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 42 publications
13
69
0
Order By: Relevance
“…It may therefore be that endogenous cortisol acts through PER1 to shift already-established circadian rhythms. A recent study in adrenalectomized rodents supported our hypothesis, showing both that endogenous cortisol was required for circadian expression of rat rPer1 and that daily cortisol administration restored rPer1 expression and entrained circadian rhythms in lung and kidney (58). Combined with our study, these results suggest that GR-mediated responses to low doses of corticosteroids are important for mammalian peripheral circadian physiology.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…It may therefore be that endogenous cortisol acts through PER1 to shift already-established circadian rhythms. A recent study in adrenalectomized rodents supported our hypothesis, showing both that endogenous cortisol was required for circadian expression of rat rPer1 and that daily cortisol administration restored rPer1 expression and entrained circadian rhythms in lung and kidney (58). Combined with our study, these results suggest that GR-mediated responses to low doses of corticosteroids are important for mammalian peripheral circadian physiology.…”
Section: Resultssupporting
confidence: 89%
“…Some peripheral clocks can be entrained independent of neuronal signals by restricted feeding times, suggesting additional clock mechanisms (9,58). Researchers have shown that either a serum shock or a DEX shock can induce circadian patterns of gene expression in tissue culture cells (3,4) and that glucocorticoids can also influence circadian rhythms in peripheral tissues (3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also shown that hydrocortisone, a glucocorticoid, can synchronize circadian clock gene expression in ex vivo mouse SCN, lung, pineal gland, salivary gland, cornea, and liver (105). Adrenalectomized rats maintain rhythmic oscillation of most clock genes in the liver and kidney, except Per1 (137). The fact that the other clock genes still oscillate suggests that glucocorticoids are not the only synchronization mechanism for the circadian clock.…”
Section: Endocrine Systemmentioning
confidence: 99%
“…However, the food-related signals that entrain the molecular clocks (food-entrainable oscillators, FEOs) in the circadian system remain unknown. In mammals, the oscillators of the circadian system respond to feeding inputs with different sensitivities, the liver being one of the most sensitive peripheral oscillators in these vertebrates (Albrecht, 2012;Damiola et al, 2000;Reddy et al, 2007;Schibler et al, 2015;Schmutz et al, 2012;Sujino et al, 2012). In teleosts, the liver is highly sensitive to the feeding/fasting cycle and food-related signals (Costa et al, 2016;del Pozo et al, 2012;Feliciano et al, 2011;López-Olmeda et al, 2010;Vera et al, 2013;Sánchez-Bretaño et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%